1976
DOI: 10.1002/aja.1001450403
|View full text |Cite
|
Sign up to set email alerts
|

The effect of frozen ovarian autografts on compensatory ovulation and steroid production in unilaterally ovariectomized rats

Abstract: In the present study rats were unilaterally ovariectomized (ULO) and the surgically removed ovary was frozen for 13 days. After allowing the remaining ovary to compensate with respect to number of ova shed, the frozen graft was thawed and transplanted subcutaneously to determine the effect on ovulation number, cycle length, uterine weight, ovarian weight and plasma levels of estradiol-17beta (E2) and progesterone. Rats ULO at 45 days of age, which received an autograft 13 days later, had a decrease in the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Callejo et al [25] showed that vaginal cytology of groups intraperitoneal and subcutaneous ovarian transplantations showed trophic maturation between days 4 and 10 after ovariectomy and insertion of the ovarian tissue implant, whereas the control group remained atrophic. In a study that was done with rats [26], at the first day of vaginal cornification after grafting, plasma estradiol-17 beta (45.8 + / − 4.0 pg/ml) was elevated in comparison to controls at metestrus (24.0 + / − 2.6 pg/ml), but plasma progesterone (21.5 + / − 4.0 ng/ml) was not different (30.6 + / − 1.7 ng/ml). Subsequently, at the first metestrus following grafting, plasma estradiol (23.0 + / − 3.5 pg/ml) was comparable to control values.…”
Section: Discussionmentioning
confidence: 99%
“…Callejo et al [25] showed that vaginal cytology of groups intraperitoneal and subcutaneous ovarian transplantations showed trophic maturation between days 4 and 10 after ovariectomy and insertion of the ovarian tissue implant, whereas the control group remained atrophic. In a study that was done with rats [26], at the first day of vaginal cornification after grafting, plasma estradiol-17 beta (45.8 + / − 4.0 pg/ml) was elevated in comparison to controls at metestrus (24.0 + / − 2.6 pg/ml), but plasma progesterone (21.5 + / − 4.0 ng/ml) was not different (30.6 + / − 1.7 ng/ml). Subsequently, at the first metestrus following grafting, plasma estradiol (23.0 + / − 3.5 pg/ml) was comparable to control values.…”
Section: Discussionmentioning
confidence: 99%